Case Study: Manipulation of Financial Reports at PT. Adisarana Wanaartha Life Insurance (Wanaartha Life) - Eka Mayasari; Sri Trisnaningsih (Formosa Journal of Applied Sciences, 2023)
This research aims to determine violations in professional ethics both from public accountants and from related parties. Violations committed by accountants can undermine the nature and integrity of accounting. When there are violations involving data manipulation, misrepresentation, or unethical behavior in accounting practices, it can shake the foundations of the integrity of the profession. The author uses the Expert Opinion Method to analyze what and how violations of the code of ethics for the public accounting profession take place. To identify efforts related to the studies discussed, the author uses references from books and several articles. From the results of this research, there are violations that have been committed in this case, including violations of integrity by manipulating financial reports by directors and financial staff, violations of professional behavior where accountants were involved in unethical actions and violations of the professional competence and prudence of accountants who failed to identify manipulation finance.